Novel Drugs for the Prevention and Treatment of Acute GVHD - Cutler, Corey; Antin, Joseph H. (Current Pharmaceutical Design, 2008)
Acute graft-vs.-host disease (GVHD) remains one of the most significant barriers to successful allogeneic stem cell transplantation, accounting for a substantial portion of early transplant-related morbidity and mortality. Acute GVHD results from the complex interaction of donor T cells and host tissues that involves recognition of major and minor histocompatibility antigens in an inflammatory milieu. The current view of the pathogeneisis of acute GVHD is that it involves three steps: (1) tissue damage from conditioning regimen, (2) donor T-cell activation and (3) an inflammatory effector phase [1]. Recent studies demonstrating the importance of chemokines and regulatory T cells in acute GVHD have added further complexity to this model [2]. Within this context, clinical strategies that mitigate host tissue damage, down-regulate activated effector donor T cells, and reduce inflammatory cytokines in the early post transplant period should be effective in treating or preventing this condition. Indeed, strategies based, at least in part, on this model have continued to aid in the development of newer agents with promise in acute GVHD. However, until recently, it is only the cellular attack on host tissues that has been specifically targeted by GVHD prophylactic mechanisms, either with the use of a variety of pharmacologic agents or graft manipulation techniques, whereas therapeutics for the treatment of established acute GVHD have invoked the role of the cytokine cascades that may perpetuate ongoing GVHD reactions. In this article, we will review the current standards for prevention and treatment of acute GVHD, and discuss novel drugs and therapeutics that hold promise for improved prevention and management of established acute GVHD.
Keywords: minor histocompatibility antigens